Flouting of Conversational Maxims In ‘Ready Player One’ Movie - I Putu Angga Andika Putra; Ni Nyoman Deni Ariyaningsih; I Wayan Juniartha (International Journal of English Learning and Applied Linguistics (IJELAL), 2021)
Conversational implicatures is an important thing that need to be interpreted in a conversation to avoid misunderstanding between the speaker and hearer so that the goal of communication can be reached. This research focuses on analysing the types of flouting maxims used by the characters in science fiction movie entitled Ready Player One since it is important to make the conversation become more effective. The theory of cooperative principle proposed by Grice used to analyze the types of flouting maxims. The researcher used descriptive qualitative method to describes the data in order to provide deep understanding about the types of flouting maxims used by the characters in the movie. The result of the research shows that there are 25 data of flouting maxim in Ready Player One movie. Flouting the maxim of quantity is the highest frequency of flouting maxim in this movie with 8 number of occurrence or 32% occurrence. Furthermore, flouting the maxim of relation and manner has the same frequency with 7 data or 28% occurrence. Flouting the maxim of quality is the lowest frequency of flouting maxim with 3 data or 12% occurrence.